2011
DOI: 10.13083/reveng.v19i1.222
|View full text |Cite
|
Sign up to set email alerts
|

Inspeção Técnica De Tratores E Pulverizadores Utilizados Em Pulverização Agrícola

Abstract: Os projetos de inspeção de tratores e pulverizadores são realizados já a longo tempo. Estes projetos buscam obter informações sobre a qualidade dos equipamentos em uso nas pulverizações agrícolas. As inspeções fundamentam-se na necessidade de que aplicações sejam eficientes evitando contaminações desnecessárias do ambiente, seres humanos e animais. Objetivou-se com este trabalho, realizar inspeção e levantar informações sobre o estado de conservação dos pulverizadores e tratores na Depressão Central do Estado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
2
7
0
7
Order By: Relevance
“…Therefore, it was observed that in 92.31% of the sprayers, the flow indicator was approved in relation to the total flow of the bar and, consequently, to the item "application volume"; however only 55.81% of the other sprayers (without flowmeter) were in accordance with the premise described in the methodology for the item at issue (Table 2). Most of the calibration errors found in the sprayers was related to the absence of the manometer or to the use of these equipments with low accuracy (determination of incorrect values), which is in agreement with what was described by Dornelles et al (2011), who report that it is necessary to pay more attention to these pressure-determining devices of the hydraulic spray circuit, since their absence may explain the ineffectiveness of many applications.…”
Section: Figure 1 Percentage Distribution Of the Occurrence Of Statisupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it was observed that in 92.31% of the sprayers, the flow indicator was approved in relation to the total flow of the bar and, consequently, to the item "application volume"; however only 55.81% of the other sprayers (without flowmeter) were in accordance with the premise described in the methodology for the item at issue (Table 2). Most of the calibration errors found in the sprayers was related to the absence of the manometer or to the use of these equipments with low accuracy (determination of incorrect values), which is in agreement with what was described by Dornelles et al (2011), who report that it is necessary to pay more attention to these pressure-determining devices of the hydraulic spray circuit, since their absence may explain the ineffectiveness of many applications.…”
Section: Figure 1 Percentage Distribution Of the Occurrence Of Statisupporting
confidence: 89%
“…When analyzing works on sprayer inspections in Brazil, it is possible to observe that the presence of leaks is one of the most frequent problems in sprayers. According to a study conducted by Alvarenga and Cunha (2010), 61.80% of the evaluated sprayers presented this type of problem, which is also in accordance with the descriptions made by Machado (2014) and Dornelles et al (2011), who describe that some kind of leaks are present in 62.00 and 64.30% of the sprayers, respectively, which are related to the lack of periodic maintenance.…”
Section: Figure 1 Percentage Distribution Of the Occurrence Of Statisupporting
confidence: 85%
See 1 more Smart Citation
“…Os pulverizadores hidráulicos de barra são as máquinas mais utilizadas na aplicação dos defensivos agrícolas com a finalidade de subdividir a calda uniforme ao longo da barra, distribuindo-as na superfície a ser tratada, e a escolha e formas de uso desses equipamentos são fundamentais para que se obtenha a ação eficaz dos defensivos agrícolas (DORNELLES et al, 2011;SILVEIRA, 2001).…”
Section: Introductionunclassified
“…KEYWORDS: Agricultural Machinery, Design, Spraying.1 | INTRODUÇÃOA maioria das aplicações de agrotóxicos em estufas agrícolas são feitas por pulverizadores costais, salvo os casos onde são retiradas algumas linhas para a máquina passar, perdendo assim espaço de cultivo. Os pulverizadores hidráulicos de barra são as máquinas mais utilizadas na aplicação dos agrotóxicos com a finalidade de subdividir a calda uniformemente ao longo da barra, distribuindo-a na superfície a ser tratada.Para tanto a escolha e formas de uso desses equipamentos são fundamentais para que se obtenha a ação eficaz dos agrotóxicos(DORNELLES et al, 2011;SILVEIRA, 2001).Segundo LOPES et al (2011), os pulverizadores costais são de baixo custo, porém possuem desvantagens como serem carregados e acionados manualmente, ficando sujeitos a variação de pressão de trabalho e a redução da capacidade operacional. Esse problema pode ser minimizado quando o acionamento e o transporte são mecanizados.…”
unclassified